Strategi Marketing Pondok Cabe Golf dalam Memanfaatkan Instagram @Pondokcabegolf untuk Meningkatkan Brand Awareness kepada Masyarakat - Alfina Wulandari; Fajar Muharam; Eni Saeni (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study examines the importance of an efficient digital marketing strategy, particularly through Instagram, to increase public understanding of sports and recreation facility brands like Pondok Cabe Golf, especially amidst increasingly fierce competition in the digital world. The purpose of this study is to evaluate the digital marketing strategy implemented by Pondok Cabe Golf on Instagram to increase brand recognition among the wider public. A descriptive qualitative approach was used, with data collected through in-depth interviews with internal marketing and public relations teams, as well as external followers. Additionally, focus group discussions, observations, and non-participant documentation collection were conducted to supplement the analysis. The results reveal that Pondok Cabe Golf has successfully implemented a digital marketing strategy that aligns with the Marketing 4.0 concept and the 5A customer journey (Aware, Appeal, Ask, Act, Advocate). This strategy involves the use of consistent visual content, engaging user interactions, and focused promotions, which have significantly increased brand awareness and built positive relationships with the audience. The findings highlight the effectiveness of Instagram as a platform for building brand recognition and community engagement. This research offers valuable insights and practical recommendations for improving digital marketing efforts in the recreation sector, particularly for businesses looking to enhance their presence in the competitive digital landscape.